Merdeka Curriculum Management for Character Development: A Comparative Study of Sociology Education - Haerudin, Atep Didin; Wasliman, Iim (Journal of Innovation and Research in Primary Education, 2025)
The contemporary educational landscape demands comprehensive approaches that combine academic excellence with student character development. This research examines Merdeka Curriculum management practices in developing student character through sociology education, focusing on planning, organizing, implementing, and controlling processes. This study employed a qualitative descriptive research design with field research approach in two senior high schools in Bandung: SMAN 23 Bandung (public) and SMA Pasundan 1 Bandung (private). Data were collected through triangulation methods including in-depth interviews with principals, vice principals, sociology teachers, and selected students, participant observations, and document analysis. Purposive sampling was used to identify key informants who had direct involvement in curriculum implementation and character education. Findings revealed that both institutions implemented systematic approaches to character development through comprehensive planning processes involving all stakeholders, clear organizational structures with task distribution based on 5W+1H principles, integrated implementation strategies that unite character education with academic learning, and multidimensional evaluation systems that track student character development progress. Effective curriculum management practices successfully integrated character development with academic learning, supporting the social-emotional and character development (SECD) framework. Implementation within sociology education contexts provides natural opportunities for character cultivation through understanding social dynamics and civic engagement, with contextual adaptations that maintain core developmental objectives.